Uma descrição sobre igrejas no modelo de células, uma análise antropológica - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
Pentecostals and the way in which they express and regiment faithful to their names, point to a possible way to understand the decision- political spaces by evangelical groups. The recent "cell model " adopted by some of these churches , among these the Church of the Foursquare Gospel bases its principles on " spiritual warfare " as taken from space ( homes, Congress ). They represent an efficient way to break through the "belief" and expressed the "desire" proselytizing of globalizing groups and resume increasing discussion surrounding the secularization and de-secularization of the modern world. The work was developed through informal entrevistais, visits the bibliography of church, three formal interviews (enough demonstrates the unhappiness that choice) accompanied by participant observation at meetings , promoted by the Church in the years 2014, 2015. Such complementary aspects adopted in the "cell vision". Organization formed by cells; and a character "revolutionary" given by faith , through " prophetic actions " . Taken as monads Tarde (2007) and cells taken as such, exemplify being in the world in its different forms.
Keywords: Pentecostais; Igreja do Evangelho Quadrangular; Modelo de Células; Política; CNPQ:: CIÊNCIAS HUMANAS